DIPLOMASI DIGITAL INDONESIA DALAM PERLINDUNGAN TENAGA KERJA INDONESIA (TKI) DI MALAYSIA PADA MASA PEMERINTAHAN PRESIDEN JOKOWI PERIODE PERTAMA - Annisya Ladeastu Putri; Ahmad Fuadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research discusses about the form diplomacy undertaken by Indonesia in seeking protection for Indonesian Migrant’s Workers who live in Malaysia. The large number of Indonesian Migrant Workers working abroad is caused by the difficulty of finding employment opportunities in the country, with the large number of Indonesian Migrant Workers working abroad, of course, will have problems that occur, where Indonesian Migrant Workers suffered torture, violence and sexual harassment. Therefore, the role of Indonesian government in protecting its citizens who are abroad is needed in this case.This study uses a Neo-realism perspective, digital diplomacy theory and the concept of human security. The theory of digital diplomacy by Lewis, explains that diplomacy uses of the internet and information and communication technologies to help achieve diplomatic objectives. The study used qualitative explanative methods, which is an analysis of the research of the data from books, journals, and official documents.The results of this study that the Indonesian government in achieving national goals and interests related to Indonesian Migrant Workers in Malaysia carries out digital diplomacy by using the internet through various digital platforms such as social media to convey Indonesian Migrant Workers issues to the public. Digital diplomacy exists not to replace, but to optimize the diplomacy that has been carried out by heads of state or representatives of other countries by focusing more on society (public). Indonesian government uses social media when handled Suyanti and Adelina cases, this diplomacy has succeeded lead public opinion through online petitions.Keywords: Digital Diplomacy, Protection, Indonesian Migrant Workers.